Financial openness and growth: short-run gain, long-run pain? - Marcel Fratzscher; Matthieu Bussière (European Central Bank (ECB), 2004)
No empirical evidence has yet emerged for the existence of a robust positive relationship between financial openness and economic growth. This paper argues that a key reason for the elusive evidence is the presence of a time-varying relationship between openness and growth over time: countries tend to gain in the short-term, immediately following capital account liberalisation, but may not grow faster or even experience temporary growth reversals in the medium- to long-term. The paper finds substantial empirical evidence for the existence of such an intertemporal trade-off for 45 industrialised and emerging market economies. The acceleration of growth immediately after liberalisation is found to be often driven by an investment boom and a surge in portfolio and debt inflows. By contrast, the quality of domestic institutions, the size of FDI inflows and the sequencing of the liberalisation process are found to be important driving forces for growth in the medium to longer term.
Keywords: F33; F34; F36; F43; 330; capital account; composition of capital flows; Economic Growth; intertemporal trade-off; liberalisation; quality of institutions; sequencing